Plants Growth Rate in Evapotranspiration continuous system reactors as the 2nd Treatment at Anaerobic-evapotranspiration system with High Strength Ammonium in Leachate Influent - Badrus Zaman; Purwanto Purwanto; Sarwoko Mangkoedihardjo (Chemical Engineering Diponegoro University, 2014)
Ammonium is one of parameter which responsible to leachate toxicity. Preliminary research was shown that the Fimbristylis globulosa (water plant), Alocasia macrorrhiza (terrestrial plant) and Eleusine indica (terrestrial grass) were potential plants for used as object in evaporation reactor system with high strength ammonium concentration in leachate treatment. This research was integrated of anaerobic system with evapotranspiration system with continuous influent using ammonium concentration in leachate was 2000 mg/l NH4-N. Plants growth rate was analyzed for 25 days operated. The result shown that average of thallus growth rate of Fimbristylis globulosa was 17,5 cm d-1. The average of leaf and thallus growth rate of Alocasia macrorrhiza was 18,1 cm d-1 and 3,2 cm d-1 respectively. The average of blade and thallus of Eleusine indica were same that was 4,7 cm d-1.This research conclude that integration system of anaerobic and evpotranspiration was be potential used for high strength ammonium in leachate treatment.